Aging Decreases L-Type Calcium Channel Currents and Pacemaker Firing Fidelity in Substantia Nigra Dopamine Neurons - Branch, Sarah Y. (Society for Neuroscience, 2014)
Substantia nigra dopamine neurons are involved in behavioral processes that include cognition, reward learning, and voluntary movement. Selective deterioration of these neurons is responsible for the motor deficits associated with Parkinson's disease (PD). Aging is the leading risk factor for PD, suggesting that adaptations occurring in dopamine neurons during normal aging may predispose individuals to the development of PD. Previous studies suggest that the unique set of ion conductances that drive spontaneous, rhythmic firing of action potentials could predispose substantia nigra dopamine neurons to selective neurodegeneration. Here we show, using patch-clamp electrophysiological recordings in brain slices, that substantia nigra dopamine neurons from mice 25–30 months of age (old) have comparable membrane capacitance and input resistance to neurons from mice 2–7 months of age (young). However, neurons from old mice exhibit slower firing rates, narrower spike widths, and more variable interspike intervals compared with neurons from young mice. Dopamine neurons from old mice also exhibit smaller L-type calcium channel currents, providing a plausible mechanism that likely contributes to the changes in impulse activity. Age-related decrements in the physiological function of dopamine neurons could contribute to the decrease in voluntary movement and other dopamine-mediated behaviors observed in aging populations. Furthermore, as pharmacological antagonism of L-type calcium channels has been proposed as a potential treatment for the early stages of PD, our results could point to a limited temporal window of opportunity for this therapeutic intervention.